Regulation of endothelial cell growth by tetrahydrobiopterin bioavailability - Rinze, R; Ruth Elisabeth Rinze (2011)
The vascular endothelium plays a critical role in the regulation of vascular homeostasis. Endothelial cell injury, loss, survival and regeneration are important aspects in the response to vascular injury and pathogenesis of vascular disease. Re-endothelialization has been shown to be a key event in vascular repair after injury. Nitric oxide (NO) produced by endothelial nitric oxide synthase (eNOS) is a key regulator of endothelial cell biology. Loss of NO bioavailability in endothelial dysfunction states is an early step in the development of atherosclerosis. The cofactor tetrahydrobiopterin (BH4) is essential for eNOS catalytic activity; when BH4 is limiting eNOS becomes enzymatically uncoupled, leading to the generation of superoxide instead of NO. eNOS function has been shown to be an important regulator of endothelial cell proliferation and survival as well as endothelial progenitor cell function. There is increasing evidence that the essential eNOS cofactor BH4 may enhance endothelial cell proliferation and endothelial progenitor function, both of which have the potential of enhancing vascular repair. The aim of this thesis is to evaluate the effect of BH4 bioavailability on endothelial cell growth in the absence and presence of vascular disease using primary endothelial cells from mice with genetic modifications in BH4 availability. Endothelial progenitor cell availability in lungs and bone marrow was investigated to address a second source for endothelial repair and potential therapeutic target. The duration of culture proved to be a major determinant of the biological phenotype of primary endothelial cells. Transgenic BH4 augmentation improved in vitro growth of primary endothelial cells in the presence but not in the absence of vascular disease. Endothelial progenitor cell content in lung tissue and bone marrow did not appear to be affected by transgenic BH4 augmentation. This thesis provides important new knowledge about the use of primary mouse endothelial cells in vascular research and insight into the role of BH4 availability on endothelial growth in a vascular disease setting.